Skip-beat! 03 - Nakamura, Yoshiki (Shojo beat manga., 2006)
Kyoko's first big assignment turns out to be more difficult than expected when she finds herself in front of the camera with an injured leg. Will she overcome the pain or will she fail her first attempt at acting?